ANALYSIS OF NON-SPECIFIC STANDARDIZED PARAMETERS ON KUMIS KUCING LEAVES (Orthosiphon aristatus (Blume) Miq.) PURPLE VARIETY - Fahrauk Faramayuda; Soraya Riyanti; Totik Sri Mariani; Rizka Khoirunnisa Guntina; Winda Nur Halimah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
One of the plants in Indonesia that can be used as a medicine is the purple variety of cat's whiskers (Orthosiphon aristatus (Blume) Miq.). This study aims to examine the quality and safety of the purple variety of Cat’s Whiskers as a raw material for traditional medicine so that it meets the requirements of being free from heavy metal, microbial, and aflatoxin contamination. The results of setting the standardization parameters on the dry material of cat’s whiskers leaves obtained drying losses, water content, total ash content, and acid insoluble ash content, respectively 8.45 ± 0.68%; 6.67 ± 1.15 %; 8.70 ± 0.09 %; 1.31 ± 0.16 %. The results of testing for the heavy metals lead (Pb) and mercury (Hg) on ??dry material and extracts were £ 0.0001 mg/kg. The results of testing the levels of microbial contamination in dry material and extracts obtained total bacteria 1.45x101 and 2.35x101 Cfu/gr, respectively. Test results for aflatoxin contamination on the dry material of Cat’s Whiskers leaves B1, B2, G1, G2 and total aflatoxin £ 0.50 ?g/kg and total aflatoxin £ 2 ?g/kg, respectively. The dried material and leaf extract of the purple variety of cat’s whiskers that were tested met the requirements stated in the regulation of the Food and Drug Supervisory Agency number 32 of 2019 about traditional medicines' safety and quality requirements.